Macroscopic and Mesoscopic Deterioration Behaviors of Concrete under the Coupling Effect of Chlorine Salt Erosion and Freezing–Thawing Cycle - Shaojie Chen (MDPI AG, 2021)
The aim of this study was to reveal the macroscopic and mesoscopic deterioration behaviors of concrete under the coupling effect of chlorine salt erosion and the freezing–thawing cycle. The rapid freezing–thawing test was carried out in a 5% chlorine salt environment. The macroscopic characteristics of concrete were analyzed by testing the mass, the relative dynamic modulus of elasticity, and the compressive strength of concrete under different freezing–thawing cycles. Using CT scanning technology and three-dimensional reconstruction technology, the pore structure, CT value, and surface deviation of concrete before and after freezing–thawing were analyzed. Based on the changes of solid volume, pore volume, and solid CT value of concrete, the calculation method of relative CT value was proposed, and the damage model was established with relative CT value as the damage variable. The results demonstrate that the mass loss rate decreases in the beginning and then increases in the process of chlorine salt erosion and freezing–thawing, and the smaller the concrete size, the greater the mass loss rate. The relative dynamic modulus of elasticity decreases gradually, slowly at the initial stage and then at a faster rate, and the compressive strength loss rate increases gradually. The pore quantity, porosity, and volume loss rate of concrete increase in a fluctuating manner, whereas the relative CT value decreases. The comprehensive analysis shows that the chlorine salt frost resistance of concrete is negatively related to the water-cement ratio when the freezing–thawing cycle is fixed. The damage model could better reflect the freezing–thawing damage degree of concrete with different water cement ratios, and the damage evolution process is well described by the Weibull function.